“Black Parade” Song: How Beyonce Criticized Racism - Awaliyah, Muzayyanah; Mustofa, Mutmainnah; Sam'ah, Iklila Ummu (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2021)
From time to time, the communication media in order to propose social criticism which is expected to provide better changes are increasingly diverse. One of them is through the delivery of messages in the lyrics of a song. Beyonce is one of the artist who often uses song as a media to propose her social criticism. In the case of the death of George Floyd a black American, murdered by the white Minesotta police (white supremacist) he released an album with one of the song in it entitled